Enzymatic Hydrolysis of Sorghum Bagasse to Readily Fermentable Sugar for Bioethanol - Soeprijanto; Katherin Indriawati; Nurlita Abdulgani (Jurnal Rekayasa Proses, 2014)
Produksi gula dari bagase sorghum menggunakan enzim selulase dan selobiase dilakukan dalam kultur batch. Tujuan percobaan adalah mempelajari pengaruh beban bagase sorghum dan waktu pretreatment kapur terhadap produksi gula dan yield gula. Pretreatment kapur dilakukan dalam 1000 ml labu leher tiga dengan beban kapur 0,1 g Ca(OH)2 /g sorghum bagasse dan ditambah dengan 500 ml air distilasi. Pengaruh waktu pretreatment (1, 2, 3, dan 4 jam) pada suhu 100°C dan pengaruh beban biomassa (5, 10, 15 % w/v) pada hidrolisis enzim untuk menghasilkan gula. Hasil penelitian menunjukkan bahwa konsentrasi gula maksimum dicapai sebesar 28,04 g/l dalam waktu pretreatment 4 jam; dan yield maksimum gula diperoleh 0,4 g glukose/ g biomassa dengan beban biomassa 5% (w/v). Kata kunci: Bagase sorghum, selulase, selobiase, hidrolisis enzim, kultur batch, pretreatment kapur Production of sugar from sorghum bagasse using enzyme of cellulase and cellobiase in a batch culture was conducted. The purpose of this experiment was to study of the effect of sorghum baggase loadings and lime pretreatment time on production and yield of sugar. Lime pretreatment was carried out in a 1000 ml three-neck flask with a lime loading of 0.1 g Ca(OH)2 /g sorghum bagasse and added with 500 ml distilled water. Effects of pretreatment time course (1, 2, 3, and 4 h) at temperature of 100°C and biomass loading (5, 10, 15 % w/v) were observed to produce sugar. The results showed that maximum concentration of sugar obtained was 28.04 g/l with a pretreatment time of 4 h; and the maximum yield of sugar obtained was 0.4 g glucose/ g biomass with a biomass loading of 5% (w/v). Keywords: Batch culture, cellulose, cellobiase, Enzymatic hydrolysis, ime pretreatment, sorghum bagasse